2020
DOI: 10.1177/1535370220908215
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan improves myocardial remodeling by inhibiting leptin autocrine activity and activating PPARγ

Abstract: The mechanism responsible for myocardial remodeling in hypertensive left ventricular hypertrophy (LVH) is complex. This study was designed to investigate the role of telmisartan in improving myocardial remodeling in hypertensive LVH and to explore the molecular mechanisms underlying the effects of telmisartan on hypertensive LVH. Hypertensive LVH was established in eight-week-old male Sprague–Dawley (SD) rats by abdominal aortic constriction. Telmisartan was intragastrically administered six weeks after surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…It may lead to cardiac remodeling through triggering its biological and physiological effect using PI3K, mitogen-activated protein kinase (MAPK) and JAK/STAT3 signaling cascade mechanism. 160 However, cardiac hypertrophy may develop because of activation of SNS and renin-angiotensin-aldosterone system. 161 Stangl et al 162 in 2000 carried out a demonstration on mice, and they confirmed that infusion of leptin leads to an increase in sympathetic activity of certain organs.…”
Section: Hyperleptinemia Aggravates Further Cardiovascular Risk Complicationmentioning
confidence: 99%
See 2 more Smart Citations
“…It may lead to cardiac remodeling through triggering its biological and physiological effect using PI3K, mitogen-activated protein kinase (MAPK) and JAK/STAT3 signaling cascade mechanism. 160 However, cardiac hypertrophy may develop because of activation of SNS and renin-angiotensin-aldosterone system. 161 Stangl et al 162 in 2000 carried out a demonstration on mice, and they confirmed that infusion of leptin leads to an increase in sympathetic activity of certain organs.…”
Section: Hyperleptinemia Aggravates Further Cardiovascular Risk Complicationmentioning
confidence: 99%
“…167 The induction of leptin signal transduction pathway through PI3K, MAPK, JAK2/STAT3 results in biological and physiological response in different tissues, including left ventricular, which is related to left ventricular hypertrophy (LVH). 160 Moreover, angiotensin II-associated myocardial remodeling may be due to the biological effect of leptin through its signal transduction. 160 In vitro investigation showed that rodent and human cardiomyocyte hyperplasia were activated by the effect of leptin.…”
Section: Hyperleptinemia Aggravates Further Cardiovascular Risk Complicationmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Telmisartan suppresses the activity of excessively released Ang-II by inhibiting the binding between Ang-II and its receptor, blocking the process of myocardial hypertrophy and protects against heart failure. 19 Recently, significant inhibitory effects of Telmisartan on MMPs and the degradation of ECM have been widely reported. 20 , 21 In the present study, the protective effect of Telmisartan on TNF-α-induced degradation of ECM in chondrocytes will be investigated to explore the potential therapeutic property of Telmisartan in OA.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of leptin receptors on the cardiomyocyte membrane has also been described, suggesting a direct effect of adipokines on myocardial function [2]. Several signalling pathways have been shown to be involved in cardiovascular regulation by leptin, including Janus activated kinase (JAK), signal transducer and activator of transcription 3 (STAT3), mitogen-activated protein (MAP) kinase, and nitric oxide [5], which are associated with a direct hypertrophic effect and can induce cardiac remodelling [2,8]. Continuous short-term leptin infusion following MI in mice causes eccentric left ventricular dilation with increased systolic function [9].…”
Section: Introductionmentioning
confidence: 99%